Unveiling (Hi)stories: Colonial Dispossession in Emile Habiby’s. The Pessoptimist and Caryl Phillips’ Crossing the River - Sabry, Mushira Salah El-Deen (AUC Knowledge Fountain, 2013)
This thesis examines the dynamics of dispossession in two (post) colonial novels: Al-waqai‘ al-ghariba fi ikhtifa’ Sa‘id abu al-nahs al-mutasha’il (1974) by the Palestinian novelist Emile Habiby (translated as The Secret Life of Saeed: The Ill-Fated Pessoptimist [1985] by Salma Khadra Jayussi and Trevor Le Gassick) and Crossing the River (1995) by West Indian novelist Caryl Phillips. Mikhail Bakhtin’s theories of the “chronotope,” “carnivalesque,” and “polyphony” are used to show how the two texts avoid using “a rhetoric of blame” (Edward Said’s expression) as their objective. Rather, both novels provide the Other’s version of an event to supplement the mainstream narrative; ultimately creating a multifaceted text that is inclusive. As a result, they creatively expose the ideological hierarchy that perpetuates dispossession, and how it affects both the oppressor and the oppressed. This study also observes parallels shared between them such as the use of racialized discourse to perpetuate the marginalization and dispossession of one group of society. The texts refer to events that the colonizer and the colonized share to expose (hi)stories that were silenced or misrepresented in the mainstream version of events to prompt the reader to explore, uncover and suspect the history written by the victors. Bakhtin’s critical theory illuminates the narrative strategies used by the works to achieve subversion of the hegemonic discourse, introduction of multiple viewpoints, and the weaving of history with imaginative episodes